An investigation on antibiotic resistance of E. coli in the Red Jungle fowl from a farm in Sepang - Joseph, Henry Michael; Bahaman, Abdul Rani; Babjee, Shaik Mohamed Amin; Zakaria, Zunita (2011)
This study was carried out to isolate and identify the normal bacterial flora in the cloaca of the Red Jungle fowl and to determine the level of antibiotic resistance in the E. coli obtained from the cloacal swabs of these birds. This study was done in a farm in Sepang, which produces Red Jungle fowl high crosses. Fifteen cloacal swabs were taken from individual birds of a one-year old female flock. The most prevalent normal flora bacteria in the cloaca of these birds were Escherichia coli and Staphylococcus aureus spp., both were present in 73% of the samples. Other bacteria isolated include Klebsiella spp., Chromobacterium spp., Achromobacter spp., Staphylococcus pseudintermidius, Staphylococcus intermidius, Staphylococcus hyicus, Corynebacterium urealyticum, Corynebacterium phocae, and Enterococcus faecalis, which were present in 7to 33% of the samples. The E. coli isolates from the Red Jungle fowl exhibit complete (100%) multiple resistance to antibiotics used in the farm, which were erythromycin, norfloxacin, and tetracycline; and penicillin G, which was never used in the farm. Although 15% of the isolates were sensitive to cephalixine, 23% were resistant. The occurrence of antibiotics resistance towards drugs that was never used in the Red Jungle fowl suggests that the antibiotic resistance may be acquired through other means other than exposure to the drug.